Pengaruh Sistem Pencatatan Barang terhadap Kinerja Gudang pada PT. Hunter Douglas Indonesia di Cikarang - Firdaus, Miskul; Ar Rasyid, Faisal Adam; Gultom, Simon (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
PT. Hunter Douglas Indonesia is a foreign interior manufacture company that produces modern curtains/window covering and architectural products. The purpose of this study is to find out the effect of the stock opname system to warehouse performance of the company in Cikarang. The method used in this study was field and library research. The study used simple linear regression, coefficient correlation, coefficient determination, and hypothesis testing to analyse the data. The result shows that t-count (5,459) is more than t-table (1,701) which means that there is a significant correlation between neat stock opname system and the warehouse performance in the company. It is proven that the hyphothesis is correct. <!--[if gte mso 9]> Dimas 15.00 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->PT. Hunter Douglas Indonesia is a foreign interior manufacture company that produces modern curtains/window covering and architectural products. The purpose of this study is to find out the effect of the stock opname system to warehouse performance of the company in Cikarang. The method used in this study was field and library research. The study used simple linear regression, coefficient correlation, coefficient determination, and hypothesis testing to analyse the data. The result shows that t-count (5,459) is more than t-table (1,701) which means that there is a significant correlation between neat stock opname system and the warehouse performance in the company. It is proven that the hyphothesis is correct.